Peningkatan Pemecahan Masalah Matematis Melalui Model Pembelajaran Inkuiri Berbantuan Aplikasi Kahoot! Pada Siswa SMA Negeri 1 Pahae Julu T.A.2022/2023 - Hendriko Yanmil Yoas Tumangger; Erlinawaty Simanjuntak (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to improve mathematical problem solving through the inquiry learning model assisted by the kahoot! in SMA Negeri 1 Pahae Julu students T.A.2022/2023. The subjects in this study were 34 students of SMA Negeri 1 Pahae Julu T.A.2022/2023 and the object of this study was an increase in mathematical problem solving through the inquiry learning model assisted by the kahoot! application. Before conducting the research, the researcher first gave a pre-test on 2 the initial observation, which was carried out in 1 meeting. From the results of data analysis, it was obtained that the average mathematical problem solving was 65.176 with the percentage of students who completed 52.94%. Therefore, an effort is needed to improve mathematical problem solving through an inquiry learning model assisted by the kahoot! in SMA Negeri 1 Pahae Julu students T.A.2022/2023. An effort made is called research. This type of research is classroom action research conducted in 2 cycles, each cycle consisting of 2 meetings. The results of data analysis in cycle I obtained an average of 71.941 mathematical problem solving with a percentage of students who completed 76.47% experienced an increase in cycle II obtained an average of 76.059 mathematical problem solving with the percentage of students who completed 79.41%. The class has completely solved the problem in cycle II research. Thus it can be concluded that the research objectives have been achieved, namely to improve mathematical problem solving through the inquiry learning model assisted by the kahoot! in SMA Negeri 1 Pahae Julu students T.A.2022/2023.